The use of dissolved inorganic carbon for the production of tomatoes (Lycopersicon esculentum Mill) - Oberholzer, Johannes Andreas (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.Sc. Agric.) -- University of Stellenbosch, 1999.